Manipulating the surface states of BiVO4 through electrochemical reduction for enhanced PEC water oxidation. Issue 9 (9th February 2023) - Yang, Peixin; Shi, Huihui; Wu, Hangfei; Yu, Duohuan; Huang, Lu; Wu, Yali; Gong, Xiangnan; Xiao, Peng; Zhang, Yunhuai
Abstract : Surface states of bismuth vanadate are manipulated by an electrochemical surface engineering strategy to achieve an efficient PEC water oxidation. Abstract : Bismuth vanadate (BiVO4 ) is a prospective candidate for photoelectrochemical (PEC) water oxidation, but its commercial application is limited due to the serious surface charge recombination. In this work, we propose a novel and effective electrochemical reduction strategy combined with co-catalyst modification to manipulate the surface states of the BiVO4 photoanode. Specifically, an ultrathin amorphous structure is formed on the surface of BiVO4 after electrochemical reduction ascribed to the breaking of the surface metal–O bonds. Photoelectrochemical measurements and first-principles calculation show that the electrochemical reduction treatment can effectively reduce the surface energy, thereby passivating the recombined surface states (r-ss) and increasing the mobility of photogenerated holes. In addition, the FeOOH co-catalyst layer further increases the intermediate surface states (i-ss) of BiVO4, stabilizes the surface structure and enhances its PEC performance. Benefiting from the superior charge transfer efficiency and the excellent water oxidation kinetics, the −0.8/BVO/Fe photoanode achieves 2.02 mA cm −2 photocurrent at 1.23 VRHE (2.4 times that of the original BiVO4 ); meanwhile, the onset potential shifts 90 mV to the cathode. These results provide a new surface engineering tactic to modify the surface states of semiconductor photoanodes for high-efficiency PEC water oxidation.